Short communication: Evaluating laying curve models and estimating genetic parameters for egg production traits in chickens - X.Y. Gui; Y.J. Li; H.Y. Yu; W.T. Zhang; X.Q. Deng; Z.F. Zhang; G.H. Hua; H. Li; H.M. Kang (Animal)
The Qingyuan partridge chicken, a highly valued indigenous breed in China, requires optimised egg production traits to maximise economic returns. This study analysed weekly egg production data from 6 776 Qingyuan partridge chickens to compare the Grossman and Wood models in fitting individual egg-laying curves and identify the most robust model for estimating egg production persistency. Genetic parameters were estimated for three key traits: age at first egg (AFE), cumulative egg number up to 28 weeks (EN), and persistency derived from the Wood model, alongside weekly egg numbers using a random regression model. Results demonstrated the Wood model’s superior performance, achieving successful curve fits for more individuals with comparable residual SEs. Moderate heritability estimates were observed for AFE (0.37 ± 0.02) and EN (0.28 ± 0.02), while persistency exhibited lower heritability (0.09 ± 0.06). Moderate to high genetic correlations emerged between AFE and EN (−0.63 ± 0.002), AFE and persistency (−0.51 ± 0.008), and EN and persistency (0.58 ± 0.008). The heritability of weekly egg numbers from weeks 1 to 28 followed a W-shaped trajectory, ranging from 0.07 to 0.19. Notably, genetic correlations between weekly egg numbers at weeks 16–19 and EN exceeded 0.91. These findings highlight the importance of selecting for egg production persistency alongside AFE and EN. Selection based on weekly egg numbers during weeks 16–19 offers a practical alternative to selection based on cumulative egg numbers, enabling early selection in breeding programmes.